Comparison of pterygomaxillary dysjunction with tuberosity separation in isolated Le Fort I osteotomies: a prospective, multi-centre, triple-blind, randomized controlled trial. Issue 2 (February 2016) - Christabel, A.; Anantanarayanan, P.; Subash, P.; Soh, C.L.; Ramanathan, M.; Muthusekhar, M.R.; Narayanan, V.
Abstract: The aim of this trial was to compare two techniques of maxillary dysjunction, with 10 mg/kg tranexamic acid as an adjuvant, in isolated non-segmented Le Fort I procedures. Two hundred patients were randomized to one of four groups: group A, pterygomaxillary dysjunction + saline; group B, tuberosity separation + saline; group C, pterygomaxillary dysjunction + tranexamic acid; and group D, tuberosity separation + tranexamic acid. Primary outcome measures were intraoperative blood loss and operating time, while the secondary outcome measures were surgical field assessment, need for blood transfusion, and duration of hospitalization. The data were analyzed using one-way analysis of variance (SPSS v. 17.0), and the level of significance was set at P < 0.05. Results revealed that group D (tuberosity separation + tranexamic acid) had the least blood loss (mean 172 ml) and shortest operating times (mean 49 min), with the best surgical field. This group also exhibited the lowest drop in postoperative haemoglobin concentration (Hb gm/dl) and packed cell volume (PCV). Five patients, all in group A, required a blood transfusion and had an extra 24 h of hospitalization. This trial revealed that the tuberosity separation technique with the use of tranexamic acid was the best protocol in producing the least blood loss, minimizing the operating time, and providing the best surgical field.